HUBUNGAN PENGETAHUAN, SIKAP, DAN PERILAKU TERHADAPKETERCAPAIAN TARGET GULA DARAH PASIEN DM TIPE 2 YANGMEMPEROLEH TERAPI ORAL ANTI DIABETES - ADE SUNGGING RIZQIAH; Lisa Aditama (Perpustakaan Universitas Surabaya, 2020)
Abstract - Diabetes mellitus type 2 diabetes is where the body is still able to produce insulin but there is resistance to insulin is not effective. The level of knowledge, attitudes and behaviors related to the achievement of diabetes blood sugar levels. The purpose of this study that analyze the relationship between knowledge, attitude and behavior of patients with type 2 diabetes who obtained oral anti-diabetic therapy towards the achievement of the target blood sugar. In a cross sectional study of non experiments using mixed methods with the number of participants as many as 30 people were outpatients at Home Diabetes UBAYA. Analysis of the data in the form of structured interviews to obtain themes and descriptive analysis to show the profile KAP and see the relationships between variables. Profile of knowledge with values that meet the assessment criteria both as much as 63.33% of participants, profile attitude with grades that meet the assessment criteria both as much as 60% of participants, behavioral profiles with grades that meet the assessment criteria both as much as 76.67% of participants with HbA1c above 7. Chi Square test results obtained significant value count greater than 0.05 quantitatively and there is a relationship between variables based on qualitative. The conclusion that the knowledge and attitude is still low.